A Juridical Analysis Of Dispute Resolution For Misleading Advertisements On Social Media - Prima Anggriawan, Teddy; Sukmawati, Herlina (CV. Inara, 2024)
Misleading advertisements on social media have become a significant issue affecting consumers and businesses. This research aims to analyze the legal framework governing dispute resolution related to misleading advertisements on social media in Indonesia. The research method used is a normative juridical approach with case studies of several well-known misleading advertisement disputes. This study finds that despite various regulations such as the Consumer Protection Act and the Electronic Information and Transactions Law (UU ITE), their implementation and effectiveness still face challenges, including a lack of legal awareness and technical barriers in law enforcement. The study also evaluates various dispute resolution methods available, such as litigation, arbitration, and mediation. The results indicate that although litigation can provide legal clarity, it often involves considerable time and costs. Arbitration and mediation offer faster and more flexible solutions but have not been fully optimized in the practice of resolving misleading advertisement disputes. The conclusion of this study is that there is an urgent need to enhance legal awareness and strengthen the existing regulatory framework. Additionally, promoting the use of alternative dispute resolution methods such as arbitration and mediation needs to be increased to achieve more effective and efficient resolutions. The research recommends enhancing cooperation between the government, social media platforms, and consumer protection agencies to create a safer and fairer environment for consumers.